2020
DOI: 10.1049/el.2019.3557
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the theoretical model of graphene pressure sensors

Abstract: In order to study the effect of shape on graphene pressure sensors, a theoretical model of polymerisation degree is proposed in this work. According to the theoretical model of polymerisation degree, it is found that the regular polygons have better sensitivity characteristics. The more the number of sides for the regular polygons, the larger the polymerisation degree, and the better the sensitivity of the graphene pressure sensors. According to the theoretical model, the polymerisation degree of the positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The sensitivity of this graphene pressure sensor is different in different pressure range, and its sensitivity is low for large pressure. In our previous work, a theoretical model of polymerisation degree was proposed to study the effect of shape on graphene pressure sensors [6]. The measured results showed that the relationship of the input with the output of graphene pressure sensor was non‐linear.…”
Section: Introductionmentioning
confidence: 99%
“…The sensitivity of this graphene pressure sensor is different in different pressure range, and its sensitivity is low for large pressure. In our previous work, a theoretical model of polymerisation degree was proposed to study the effect of shape on graphene pressure sensors [6]. The measured results showed that the relationship of the input with the output of graphene pressure sensor was non‐linear.…”
Section: Introductionmentioning
confidence: 99%